Identification of Preschoolers' Mental Preparation for School - Aziza Abdusamatovna, Bobokeldiyeva; Munavvar Abdullayevna, Sheraliyeva (International Journal of Psychosocial Rehabilitation, 2020)
This article covers how to determine the mental preparedness of a preschool child and how much the child will be ready to attend school at the age of both Ali and physically and mentally. It is also noted that the child of school age is not only a special specialist, but also parents are responsible for preparing their child for the first time in every possible way to go to school.